83.5k views
5 votes
Which expression is equivalent to?

Which expression is equivalent to?-example-1
User YEVY
by
5.3k points

2 Answers

4 votes

Answer:


4x

Explanation:

The given expression is


x+2+[4x-(x^2+6x+8)/(x+4) ]

Let us first of all split the middle term of the quadratic trinomial to get,


=x+2+[4x-(x^2+2x+4x+8)/(x+4) ]


We simplify to get;


=x+2+[4x-(x(x+2)+4(x+2))/(x+4) ]

We factor to obatin,


=x+2+[4x-((x+2)(x+4))/(x+4) ]


We cancel the common factor to get,



=x+2+[4x-(x+2)]


This simplifies to,


=x+2+4x-x-2


This gives us,


=4x








User Sarpdoruk Tahmaz
by
5.3k points
4 votes

answer

4x

steps


x+2 + (4x-(x^2+6x+8)/(x+4) )

factor x^2 + 6x + 8

product=8 and sum =6

4 times 2 = 8

4 + 2= 6

(x+4)(x+2)


x+2 + (4x-((x+4)(x+2))/(x+4) )

Cancel out x+4 at the top and bottom

x + 2 +(4x -(x+2))

Now we remove the parenthesis

x + 2+4x -x-2

4x

So the final answer is 4x


User Andrei Mankevich
by
5.5k points